สมบัติของคอนกรีตมวลรวมหินควอร์ตไซต์ผสมเถ้าปาล์มนํ้ามันมีนํ้าหนัก สูญหายหลังเผาสูง (Properties of Quartzite Aggregate Concrete Blended with Oil Palm Ash with High Loss on Ignition) - ตันนโยภาส ดนุพล; ลิขิตวานิช ศรวิษฐ; ชัยวิชิต นันทวิทย์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ การศึกษาเชิงทดลองครั้งนี้เพื่อศึกษาสมบัติของคอนกรีตมวลรวมส่วนใหญ่เป็นหินควอร์ตไซต์จากเหมือง ดีบุกเก่าผสมเถ้าปาล์มนํ้ามัน ทดสอบสมบัติมวลรวม ได้แก่ ความหนาแน่นหลวมและความหนาแน่นแน่น การคละขนาด ความถ่วงจำเพาะ การดูดซึมนํ้า ดัชนีความแบนและดัชนีความยาว การขัดสีแบบ ลอสแองเจลิส ค่ากระแทก กำลังแรงกดจุด ส่วนเถ้าปาล์มนํ้ามันที่มีนํ้าหนักสูญหายหลังเผาสูงแทนที่ ปูนซีเมนต์ปอร์ตแลนด์ประเภทที่ 1 ในอัตราส่วน 10 20 และ 30% โดยนํ้าหนัก มีอัตราส่วนนํ้าต่อวัสดุ ประสาน 0.45 คงที่ตลอดการทดลอง หล่อคอนกรีตทรงลูกบาศก์ขนาด 10 x 10 x 10 เซนติเมตร ไม่บ่มนํ้า และบ่มนํ้าที่ 7 และ 28 วัน ครบกำหนดนำตัวอย่างคอนกรีตทดสอบ ความหนาแน่นรวม การดูดซึมนํ้า ความแข็งแบบชอร์ ความต้านทานไฟฟ้า ทนทานต่อแมกนีเซียมซัลเฟตกำลังอัด และ วิเคราะห์แร่ด้วยวิธีการเลี้ยวเบนรังสีเอกซ์และโครงสร้างจุลภาคด้วยกล้องจุลทรรศน์อิเล็กตรอนแบบส่องกราด ผลศึกษาครั้งนี้ได้คอนกรีตผสมเถ้าปาล์มนํ้ามัน 10% อายุบ่ม 28 วัน มีกำลังอัด 67.55 เมกะพาสคัล ความทนทานต่อแมกนีเซียมซัลเฟตของคอนกรีตผสมเถ้าปาล์มค่อนข้างตํ่ากว่าของคอนกรีตควบคุม Abstract In this experimental investigation was carried out the properties of concrete containing waste rock aggregate which had mostly quartzite from former tin mine blended with oil palm ash (OPA). Aggregate property tests were conducted on loose and dense density, fineness modulus, specific gravity, water absorption, flakiness and elongation index, Los Angeles abrasion, impact value, and point load strength. OPA with high loss on ignition was used as a pozzolanic material partially replaced ordinary Portland cement type 1 in proportion of 10, 20 and 30wt.%. The water to binder ratio 0.45 was kept constant throughout this study. The concrete specimen used in this study was cubic with the size of 10 x 10 x 10 cm and classified as non-curing and cured in water for 7 and 28 days. The concrete specimens were tested on bulk density, water absorption, Shore hardness, electrical resistance, compressive strength and magnesium sulfate durability. Also, scanning electron microscope was used to analyze microstructure and mineral phase via X-ray diffraction. From this studied result, it was provided that the 28-day compressive strength of concrete blended with 10% OPA was 67.55 MPa. Magnesium sulfate durability of concrete blended with OPA was rather lower than control concrete.